TESTICULAR CYCLE OF Devario aequipinnatus (TELEOSTEI, CYPRINIDAE) - Araujo Chagas, Jumma Miranda [UNESP]; Ninhaus-Silveira, Alexandre [UNESP]; Verissimo-Silveira, Rosicleire [UNESP] (Inst Pesca, 2016)
The presente study describes the testicular structure, spermatogenesis and maturation phases in the Devario aequipinnatus, a species with great potential for use as a biological model for animal experimentation. The testes in D. aequipinnatus were classified as tubular anastomosing with unrestricted spermatogonial distribution. Were observed four phases of testicular maturation based on the changes of the testicular germinal epithelium associated with the stages of germ cells present: Early Maturation, Mid Maturation, Late Maturation and Regression. Due to the phylogenetic proximity, testicular morphology D aequipinnatus is similar to other Cyprinideos, example, zebrafish (Danio rerio), which corroborates the hypothesis that the use of D aequipinnatus as a biological model for animal experimentation.
Keywords: reproductive phases; germinal epithelium; Danio; spermatogenesis; fish